Nitrate supply regulates tissue calcium abundance and transcript level of Calcineurin B-like (CBL) gene family in wheat - Adavi B, Sandeep (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.